Generalized Review on EVD and Constraints Simplex Method of Materials Properties Optimization for Civil Engineering - Onyelowe, Kennedy C; Alaneme, George; Bui Van, Duc; Nguyen Van, Manh; Ezugwu, Charles; Amhadi, Talal; Sosa, Felix; Orji, Francis; Ugorji, Benjamin (Civil Engineering Journal, 2019)
Extreme vertex design (EVD) has been adapted to be used in the modeling of the behavior of mixture experiments in civil engineering. This method has been in use since the 1970s and has be prevalent in the field of medical science. Various other methods of design of experiments have been used in engineering but neither has EVD being used particularly in civil engineering. This review is presented to serve as a hub or guide for subsequent exercise where concrete production, asphalt production or modification, soils stabilization and concrete improvement or water treatment would be studied with the help EVD. Its ability to fix design points and centroids has been reviewed in this work. EVD operates with various algorithms and depends on the order or condition of problems to be solved. The XVERT algorithm working on Minitab and Design Expert platform was adopted in this review work because of its efficiency in handling quadratic model problems like the four cases reviewed in the present work. From the four special cases, it can be asserted that there is a confidence in the use of EVD to develop the constraints, design the experimental factor space, design the mix proportions, and validate the models resulting from these procedures after experimental specimens are tested to determine the responses.